2021
DOI: 10.3390/cells10020320
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Intermittent Mild Whole-Body Hypothermia Is Therapeutic in a Mouse Model of ALS

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease that causes motor neuron degeneration. There are no cures or effective treatments for ALS. Therapeutic hypothermia is effectively used clinically to mitigate mortality in patients with acute acquired brain injury and in surgical settings to minimize secondary brain injury. The efficacy of therapeutic hypothermia in chronic neurodegenerative disorders has not been examined. We tested the hypothesis that mild hypothermia/cold acclimation is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Sirtuin6 is also cold-inducible and regulates thermogenesis [ 102 ]. In this regard, Sirtuin6 is of interest because repetitive periodic whole-body hypothermia can extend the lifespan of ALS mice [ 103 ]. hSOD1 mus -G37R mice also had hypermethylation of mex3d gene.…”
Section: Discussionmentioning
confidence: 99%
“…Sirtuin6 is also cold-inducible and regulates thermogenesis [ 102 ]. In this regard, Sirtuin6 is of interest because repetitive periodic whole-body hypothermia can extend the lifespan of ALS mice [ 103 ]. hSOD1 mus -G37R mice also had hypermethylation of mex3d gene.…”
Section: Discussionmentioning
confidence: 99%
“… 26 ). Multiple studies have observed alterations in skeletal muscle metabolic pathways, including altered expression of mitochondrial uncoupling proteins 27 , 28 in mouse models and human biopsies associated with modulation of metabolic flexibility (i.e. the balance between the use of glucose and fatty acids as a fuel substrate).…”
Section: Muscle Autonomous Phenotype In Alsmentioning
confidence: 99%
“…In addition to the review articles, this Special Issue also contains three papers reporting original research relating to the PT. In a mouse model of ALS, Martin et al report that the therapeutic efficacy of mild whole-body hypothermia is at least partly linked to the inactivation of the mPTP [ 6 ]. Readnower et al used a genetic model of mPTP inhibition—mice lacking the CypD encoding gene Ppif —to establish that the mPTP is an important drug target in protection against traumatic brain injury [ 7 ].…”
mentioning
confidence: 99%